Descriptive parameters of the erythrocyte aggregation phenomenon using a laser transmission optical chip - Toderi Cicchini, Martín Alejandro (2017)
The study of red blood cell (RBC) aggregation is of great interest because of its implications for human health. Altered RBC aggregation can lead to microcirculatory problems as in vascular pathologies, such as hypertension and diabetes, due to a decrease in the erythrocyte surface electric charge and an increase in the ligands present in plasma. The process of erythrocyte aggregation was studied in stasis situation (free shear stresses), using an optical chip based on the laser transmission technique. Kinetic curves of erythrocyte aggregation under different conditions were obtained, allowing evaluation and characterization of this process. Two main characteristics of blood that influence erythrocyte aggregation were analyzed: the erythrocyte surface anionic charge (EAC) after digestion with the enzyme trypsin and plasmatic protein concentration in suspension medium using plasma dissolutions in physiological saline with human albumin. A theoretical approach was evaluated to obtain aggregation and disaggregation ratios by syllectograms data fitting. Sensible parameters ( Amp 100 , t 1 \ 2 ) regarding a reduced erythrocyte EAC were determined, and other parameters (AI, M-Index) resulted that are representative of a variation in the plasmatic protein content of the suspension medium. These results are very useful for further applications in biomedicine.